Treatment of A First Unprovoked Seizure - J Gordon Millichap (Pediatric Neurology Briefs, 2003)
The Quality Standards Subcommittee of the AAN and Practice Committee of the CNS have reviewed published literature to determine when to begin treatment after a first unprovoked seizure, risk of recurrence, prevention of recurrence, development of chronic epilepsy, and side effects of AEDs.